2006
DOI: 10.1017/s0269888906001020
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the agent technology chasm: Lessons, experiences and challenges in commercial applications of agents

Abstract: Agent software technologies are currently still in an early stage of market development, where, arguably, the majority of users adopting the technology are visionaries who have recognized the long-term potential of agent systems. Some current adopters also see short-term net commercial benefits from the technology, and more potential users will need to perceive such benefits if agent technologies are to become widely used. One way to assist potential adopters to assess the costs and benefits of agent technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 14 publications
(11 reference statements)
0
37
0
1
Order By: Relevance
“…With the agent paradigm increasingly becoming a popular and successful way for modelling complex systems (Munroe et al, 2006), methodologies for agent-oriented software engineering have become an important research field. Several such methodologies have been proposed, such as Tropos (Bresciani et al, 2004), Prometheus (Padgham and Winikoff, 2004), Gaia (Zambonelli et al, 2003), INGENIAS (Pavón and Gómez-Sanz, 2003), and ROADMAP (Juan et al, 2002).…”
Section: Agent-oriented Modellingmentioning
confidence: 99%
“…With the agent paradigm increasingly becoming a popular and successful way for modelling complex systems (Munroe et al, 2006), methodologies for agent-oriented software engineering have become an important research field. Several such methodologies have been proposed, such as Tropos (Bresciani et al, 2004), Prometheus (Padgham and Winikoff, 2004), Gaia (Zambonelli et al, 2003), INGENIAS (Pavón and Gómez-Sanz, 2003), and ROADMAP (Juan et al, 2002).…”
Section: Agent-oriented Modellingmentioning
confidence: 99%
“…Indeed industrial practitioners are often scared by the thought of an agent autonomously learning and changing behaviours (Munroe, et al, 2006).…”
Section: Learningmentioning
confidence: 99%
“…This approach has attracted an increasing amount of interest from the research community and has demonstrated its potential in many fields, such as: (i) working with different types of distributed devices (e.g., sensor networks, mobile phones, and personal computers), (ii) enabling various types of communication and data exchange (e.g., audio and video), and (iii) ability to dynamically adapt to the ever changing requirements and dynamic operating environment (Munroe et al, 2006), (Pěchouček and Mařík, 2008), (Dam and Winikoff, 2013).…”
Section: Introductionmentioning
confidence: 99%